2018
DOI: 10.3390/ijerph15112351
|View full text |Cite
|
Sign up to set email alerts
|

Lead Exposure in Low and Middle-Income Countries: Perspectives and Lessons on Patterns, Injustices, Economics, and Politics

Abstract: Lead exposure is a legacy issue that continues to affect vulnerable population groups globally, but particularly in low and middle-income countries (LMICS). We take a multi-disciplinary approach to examine the patterns of lead exposure in these countries, discuss the underlying injustices and socio-political causes, and the economic costs that are associated with exposure. We conclude with some lessons we drew from our discussion of lead across the disciplines and advocate for a number of approaches to solving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 125 publications
(151 reference statements)
0
72
0
1
Order By: Relevance
“…Epidemiological and experimental evidence across a range of exposures indicate that chronic exposure to heavy metals and metalloids, including lead, arsenic, and cadmium, are associated with CVD development [1,55,56], though most evidence is from high-income countries with low-to-moderate levels of exposure. The full extent of heavy metal exposure in LMICs is unknown due to few countries having biomonitoring programs in place, though evidence from individual studies indicates substantially higher exposures than in high-income countries [57][58][59].…”
Section: Lead Cadmium and Arsenicmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological and experimental evidence across a range of exposures indicate that chronic exposure to heavy metals and metalloids, including lead, arsenic, and cadmium, are associated with CVD development [1,55,56], though most evidence is from high-income countries with low-to-moderate levels of exposure. The full extent of heavy metal exposure in LMICs is unknown due to few countries having biomonitoring programs in place, though evidence from individual studies indicates substantially higher exposures than in high-income countries [57][58][59].…”
Section: Lead Cadmium and Arsenicmentioning
confidence: 99%
“…Lead was one of the first pollutants to receive global attention following elucidation of its neuro-cognitive effects in children [58]. Despite remarkable global decreases in blood lead levels following bans on leaded gasoline in many countries [60,61], pockets of high exposure persist among people living near industry and in areas with less environmental regulation [58,62,63].…”
Section: Lead Cadmium and Arsenicmentioning
confidence: 99%
See 1 more Smart Citation
“…They are exposed to lead from a range of long-standing and emerging sources, emanating from the formal (regulated) and informal sectors [13]. Their elevated levels of lead exposure stymie children's development, as well as the socio-economic prospects for families, communities and nations [12,[14][15][16]. The distribution of elevated blood lead levels is socially stratified, with poorer communities exhibiting significantly elevated burdens of lead exposure, which increases or entrenches social inequalities [16].…”
Section: Discussionmentioning
confidence: 99%
“…Populations with certain sociodemographic and socioeconomic characteristics are more susceptible to lead exposure [29] For example, populations in countries with poor economic development are at highest risk of household exposures [30] as cited in Kordas et al [29]. Several studies in other parts of the world reported associations between sociodemographic characteristics and sources of lead, particularly in developed countries, where BLLs are associated with lower socioeconomic status [31].…”
Section: Association Between Sociodemographic Characteristics and Soumentioning
confidence: 99%